CD4 T-cell aging exacerbates neuroinflammation in a late-onset mouse model of amyotrophic lateral sclerosis - Shir Zaccai; Anna Nemirovsky; Livnat Lerner; Leenor Alfahel; Ekaterina Eremenko; Adrian Israelson; Alon Monsonego (Journal of Neuroinflammation, 2024)
Abstract Amyotrophic lateral sclerosis (ALS) is an adult-onset progressive neurodegenerative disorder characterized by the loss of upper and lower motor neurons in the brain and spinal cord. Accumulating evidence suggests that ALS is not solely a neuronal cell- or brain tissue-autonomous disease and that neuroinflammation plays a key role in disease progression. Furthermore, whereas both CD4 and CD8 T cells were observed in spinal cords of ALS patients and in mouse models of the disease, their role in the neuroinflammatory process, especially considering their functional changes with age, is not fully explored. In this study, we revealed the structure of the CD4 T-cell compartment during disease progression of early-onset SOD1G93A and late-onset SOD1G37R mouse models of ALS. We show age-related changes in the CD4 T-cell subset organization between these mutant SOD1 mouse models towards increased frequency of effector T cells in spleens of SOD1G37R mice and robust infiltration of CD4 T cells expressing activation markers and the checkpoint molecule PD1 into the spinal cord. The frequency of infiltrating CD4 T cells correlated with the frequency of infiltrating CD8 T cells which displayed a more exhausted phenotype. Moreover, RNA-Seq and immunohistochemistry analyses of spinal cords from SOD1G37R mice with early clinical symptoms demonstrated immunological trajectories reminiscent of a neurotoxic inflammatory response which involved proinflammatory T cells and antigen presentation related pathways. Overall, our findings suggest that age-related changes of the CD4 T cell landscape is indicative of a chronic inflammatory response, which aggravates the disease process and can be therapeutically targeted.